Attitude towards purchase intention for local brand automobiles manufactured locally: a comparative study - Chinedu, Anyanwu Hilary; Haron, Sharifah Azizah; Hashim, Ahmad Hariza; Jo, Ann Ho (Jilin University, 2022)
Broader accessibility of foreign products to provincial consumers and its resultant effects on local brand production necessitated calls for consumers’ formation of favorable attitudes towards local automobiles manufactured locally in developing countries. While a continuum of studies portrayed consumers from developing countries as people with unfavorable attitudes towards local products due to their lower ethnocentric tendencies, a remarkable shift towards this belief has emerged. About 382 samples of potential consumers of Innoson vehicle manufacturing (IVM), and 373 samples of Proton automobile company collected via mall-intercept was used to compare attitudes towards purchase intention for local brand automobiles manufactured in Nigeria and Malaysia. Results revealed that IVM potential consumers exhibited more favorable attitudes than Proton automobile potential consumers. Structural equation modeling (SEM) using AMOS showed that the two models demonstrated a good fit. However, Proton model showed better fitness indices compared to IVM model. The results further depicted that consumer ethnocentrism has a significant influence on attitude towards purchase intention for local brand automobiles manufactured in Nigeria and Malaysia. Proton model revealed that collectivism significantly influenced attitude towards purchase intention for local brand automobiles manufactured locally, whereas collectivism had no significant influence in IVM model. Therefore, favorable attitudes towards purchase intention for local products are unlikely without consumer ethnocentrism, irrespective of consumers’ collectivistic tendencies. Implications of the results are also discussed.